PELAYANAN PUBLIK PADA KELURAHAN PEMATANGKAPAU KECAMATAN KULIM KOTA PEKANBARU TAHUN 2023-2024 - Akhidah, Yola Misi; ', Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Public service providers as a consequence of the implementation of regional autonomy, especially after the enactment of Law Number 23 of 2014 concerning Regional Government. However, various issues have arisen among the community, it turns out that the service rights received by the community have not met the expectations of all good parties. Law no. 25 of 2009, what is meant by public service is an activity or series of activities in order to fulfill service needs in accordance with statutory regulations for every citizen and resident regarding goods, services and/or administrative services provided by public service providers. The problem in this research is that public services in Pematangkapau Village are still not effective and efficient. The service provided is still not optimal. These complaints are about the service taking a long time and there is still work that cannot be completed as it should be. After the expansion of the Pematangkapau subdistrict office, there is still a lack of facilities and infrastructure which can then hinder the provision of services. This research uses a qualitative approach. The types of data are primary data and secondary data, primary data is obtained directly from informants. Meanwhile, secondary data is supporting or strengthening primary data. Data collection techniques were carried out by means of interviews and documentation. The results of research conducted regarding the evaluation of public services using this theory. Through interviews with informants, it was seen that the awareness of the Pematangkapau subdistrict office employees in carrying out their duties was considered by the majority of informants to be good, although there were still several shortcomings, such as sometimes some employees arriving late and incomplete infrastructure and uncertain service times. Factors inhibiting the implementation of public services at the Pematangkapau Subdistrict office, Kulim District, Pekanbaru City are the lack of employee resources and the lack of facilities and infrastructure. Keywords: Public services, expansion, sub-district